2018
DOI: 10.1038/s41467-018-03604-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatially heterogeneous dynamics in a metallic glass forming liquid imaged by electron correlation microscopy

Abstract: Supercooled liquids exhibit spatial heterogeneity in the dynamics of their fluctuating atomic arrangements. The length and time scales of the heterogeneous dynamics are central to the glass transition and influence nucleation and growth of crystals from the liquid. Here, we report direct experimental visualization of the spatially heterogeneous dynamics as a function of temperature in the supercooled liquid state of a Pt-based metallic glass, using electron correlation microscopy with sub-nanometer resolution.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 72 publications
4
81
1
2
Order By: Relevance
“…The obvious difference in the slopes demonstrates that the atomic structure of the particles significantly influences the coalescence kinetics. Apparently, the coalescence of MGNs is dominated by surface diffusion, in line with the classical coalescence theory of two spherical particles with isotropic surface tension 26,34 . In contrast, the coalescence of crystalline particles appears to be influenced by a facet mediated surface diffusion, which can increase the exponent n from 1/7 up to ∼1/3 as suggested by KMC simulations 20,35 .…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The obvious difference in the slopes demonstrates that the atomic structure of the particles significantly influences the coalescence kinetics. Apparently, the coalescence of MGNs is dominated by surface diffusion, in line with the classical coalescence theory of two spherical particles with isotropic surface tension 26,34 . In contrast, the coalescence of crystalline particles appears to be influenced by a facet mediated surface diffusion, which can increase the exponent n from 1/7 up to ∼1/3 as suggested by KMC simulations 20,35 .…”
Section: Resultssupporting
confidence: 77%
“…For macroscopic particles (>1 mm), the coarsening is usually accomplished by viscous flow regardless of crystalline and amorphous structures 24,25 . However, the coarsening kinetics and underlying mechanisms of MGNs at high temperatures remain largely unknown although fast surface dynamics of nanostructured MGs have widely been observed in both experiments 26,27 and simulations 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the STZ theory is based on the assumption of structural heterogeneity in metallic glasses as structural origins of shear localization and shear softening, a distinct relationship between the structural inhomogeneity and macroscopic mechanical properties of metallic glasses has not been established. Extensive computational simulations 12 15 and experimental characterizations 16 19 have demonstrated that the structural inhomogeneity of metallic glasses is associated with nanoscale structure fluctuation, which possibly inherits from spatially heterogeneous dynamics in low-temperature supercooled liquids prior to glass transition. The assumption of soft or liquid-like regions in spatial heterogeneity has been widely used to account for the anelastic deformation 20 26 and the structural rejuvenation 27 29 of metallic glasses.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some new ndings have suggested that the surface of nanoscale materials has a much more exible structure. 31 The possible mechanism for stabilization of the solid-solution state on the nanoscale is considered to be relaxation of local strain by the more exible structure of nanoparticles, as compared to with the rigidity of bulk material structures (Fig. S33B †).…”
Section: Thermal Stabilitymentioning
confidence: 99%